The Jossey-Bass handbook of nonprofit leadership and management - Herman, Robert D., 1946-; Renz, David O. (David Owen) (San Francisco : Jossey-Bass, 2010)
"This is the Third Edition of the bestselling nonprofit management reference and text called the "big green book." Based on updated research, theory, and experience, this comprehensive edition offers practical advice on managing nonprofit organizations and addresses key aspects such as board development, strategic planning, lobbying, marketing, fundraising, volunteer management, financial management, risk management, and compensation and benefits. New chapters cover developments in such areas as social entrepreneurship, financial leadership and capital structure, accountability and transparency, and the changing political-legal climate. It includes an instructor's manual."--
Includes bibliographical references and index.
Keywords: Nonprofit organizations -- Management; Print books